Dimensi Psikis Manusia Dalam Surat An-Nazi’at Ayat 40-41 Perspektif Tafsir Jailani dan Tasawuf: Studi Tematik Tentang Pengendalian Diri - Bara, Sarah Kumala B; Safria Andy (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The human being is a aspect of a human soul or mental soul that includes mental, emotion, and spiritual conditions. In the context of the Qur’an, psychics are often represented by the term nafs, spirit, and qolb, who describes the dimensions of the human soul thoroughly based on the perspective of the Qur’an, especially the interpretation of Q.S.An-Nazi’at verse 40-41. Syaikh Abdul Qadir al-Jailani emphasized that lust is a major barrier in the spiritual journey. It is then confirmed that lust is the primary barrier in spiritual journey to Ma ‘rufatullah and interpret the An-Nazi’at verse 40-41 by emphasizing that self-control is a manifestation of piety, and in a book of interpretation attributes that self-control with the concept of a euphemistic that emphasizes the soul purification. The peace of mind according to Al-Jailani is also closely related to the clarity of thought and heart. In his works, he insists that the clear heart is a mirror that must always be cleaned of sin and malice and arrogance of pleasure. Tasawuf as a way to the sincerity of a servant who left his lust due to Allah Swt., he will get safety from His punishment and has His grace. In its view, self-control is a process in a handbag that leads to maqam takhalli (self-cleaning), tahalli (decorating herself with kindness), and tajalli (revealed the Divine light in the soul). This study uses a qualitative-dative method with the literature approach as well as the engineering of thematic interpretation analysis.